Hubungan Usia, Jenis Kelamin dan Jenis Kanker Terhadap Kualitas Hidup Anak dengan Kanker - Wiwi Kustio Priliana; Fika Nur Indriasari; Etik Pratiwi (LPPM STIKES NOTOKUSUMO YOGYAKARTA, 2018)
Background: Cancer is a disease with a high mortality rate. The quality of life in children with cancer describes the potential impact of disease or treatment that affects the function or aspects of life seen from the perception of the patient. Factors affecting the quality of life include age, gender, education, occupation, risk behavior, chronic illness, mental disorders, and economic status. Objective : Know how the quality of life of children with cancer and how the relationship of age, gender, and type of cancer to the quality of life of children with cancer in Yogyakarta. Methods: The type of this research is analytic observational with a cross-sectional design. Sampling technique with the purposive sample while data collection technique with questionnaire sheet. This research was conducted at Yayasan Rumah Bunda with research instrument using PedsQL (Pediatric Quality of Life Inventory). Data analysis using Pearson and Spearman correlation test to assess bivariate relationship. Result: Age of children related to the quality of life of children with cancer. Sex of the child is not related to the quality of life of children with cancer. Types of child cancers are not related to the quality of life of cancer children. Conclusion: The relationship between the child's age, sex, and the type of cancer have a weak relationship to the quality of life in children with cancer.